Statistical Approach for Validating Static Threshold in Fast Attack Detection - Abdollah, M. F.; Mas'ud, M. Z.; Yusof, R.; Selamat, S. R. (Universiti Teknikal Malaysia Melaka, 2010)
Network has growth to a mammoth size and becoming more complex, thus exposing more services it offers towards multiple types of intrusion vulnerabilities. One method to overcome intrusion is by introducing intrusion detection system (IDS)for detecting the threat before it can damage the network resources.